1982
DOI: 10.3102/00028312019003443
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thematic-Fantasy Play Training on the Development of Children’s Story Comprehension

Abstract: This study examined the effects of three modes of story reconstruction training on the development of children’s story comprehension. One hundred and eight children in grades K-2 were assigned randomly to one of three training conditions: thematic-fantasy play, adult-lead discussion, or drawing. Children were read three books on separate occasions and exposed to the appropriate conditions in relation to each book. Story comprehension data, as measured by a two-factor, criterion-referenced test and a retell tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(35 citation statements)
references
References 10 publications
3
29
1
2
Order By: Relevance
“…Table 3 presents a comparison of means. The fact that students made gains in narrative is consistent with previous research (Nielsen, 1993;Pellegrini & Galda, 1982), which found that repeated and active experiences with narrative, such as acting out and using puppets to support retellings, can affect students' demonstration of narrative understanding and production. While specific vocabulary can be taught explicitly, narrative is developed with repeated experiences with stories (Morrow, 1988;Senechal, LeFevre, Thomas, & Daley, 1998).…”
Section: Narrativesupporting
confidence: 88%
See 1 more Smart Citation
“…Table 3 presents a comparison of means. The fact that students made gains in narrative is consistent with previous research (Nielsen, 1993;Pellegrini & Galda, 1982), which found that repeated and active experiences with narrative, such as acting out and using puppets to support retellings, can affect students' demonstration of narrative understanding and production. While specific vocabulary can be taught explicitly, narrative is developed with repeated experiences with stories (Morrow, 1988;Senechal, LeFevre, Thomas, & Daley, 1998).…”
Section: Narrativesupporting
confidence: 88%
“…Pellegrini and Galda (1982) engaged K-2 children in drawing, adult-led discussion, or thematic fantasy play (reenactment) following the reading of a story. The results indicated that reenactment significantly affected story comprehension.…”
Section: Narrativementioning
confidence: 99%
“…The findings in these studies were not entirely consistent and also demonstrated deaf children's play behaviors were inferior when compared to those of their hearing peers. Additionally, research suggests that play behavior is influenced by the play contexts and play materials, (Henniger, 1985;Larson, Greenfield & Land, 1990;McLoyd, 1983;Pellegrini & Galda 1982;Pellegrini, Galda & Rubin, 1984;Shim, Herwig & Shelley, 2001) and play partners (Doyle et al, 1980;Matthews, 1978;Hadley & Rice, 1991;Hartup, 1978Hartup, , 1983Howes, 1983;Howes et al, 1994;Rice, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research suggests that play behavior is influenced by the play contexts and play materials (Henniger, 1985;Larson et al, 1990;McLoyd, 1983;Pellegrini & Galda, 1982;Pellegrini et al, 1984;Shim et al, 2001) and play partners (Doyle et al, 1980;Matthews, 1978;Hadley & Rice, 1991;Hartup, 1978;Howes, 1983;Howes et al, 1994;Rice, 1993). Rubin's (2001) play observation scale included social play behavior categories (solitary, parallel, and cooperative play behaviors) and cognitive play behaviors categories (functional play, constructive play, pretend/dramatic play, and games with rules).…”
Section: Introductionmentioning
confidence: 99%
“…Dadas las semejanzas entre juego y narración, una serie de estudios (Nicolopoulou et al, 2006;Nicolopoulou et al, 2015;Pellegrini, 1984;Pellegrini & Galda, 1982) Por su parte, Pellegrini y Galda (1982) evaluaron la reconstrucción de un cuento por parte de niños preescolares y de segundo grado en tres condiciones -a partir de una situación de juego simbólico, de una conversación guiada por un adulto o de un dibujo-. Los resultados evidenciaron que para los niños de preescolar, la situación de juego simbólico fue el facilitador más eficaz para las diversas medidas de comprensión consideradas en el estudio.…”
Section: Introductionunclassified